A randomised controlled trial on effects of contact and non-contact laser photocoagulation therapy on ocular surface in patients with proliferative diabetic retinopathy - Wan Wei, Loo (2015)

(untitled)
Introduction Ocular surface changes are commonly seen in diabetes mellitus. It can be made worse by either contact or non-contact laser photocoagulation (LP) in proliferative diabetic retinopathy (PDR). Objective The aim of the study is to evaluate the effects of contact and non-contact LP therapy on ocular surface changes and Ocular Surface Disease Index (OSDI) score in patients with PDR. Methods This is a randomized controlled trial in Hospital Universiti Sains Malaysia from June 2013 to May 2015. Patient with PDR was selected and randomized into 2 groups by using random sampling envelope method, Contact LP group and Non-contact LP group. Patients were evaluated for Schirmer test, tear film break-up time (TBUT) and assessment of OSDI questionnaire before treatment and 3 months post laser treatment. Statistical analyses were performed using SPSS version 22.0. Results A total of 60 eyes from 34 patients were recruited (Contact LP: 30 eyes from 17 patients and Non-contact LP: 30 eyes from 17 patients). There was no significant difference in mean change of the Schirmer test (p=0.378) at 3 months post treatment between the two groups. Although there was significant reduction in TBUT at 3 months post laser in Contact LP group (p=0.038), but there was no significant difference in mean change of TBUT between the two groups (p=0.549). There was significant increased in mean change of OSDI score at 3 months post treatment in Contact LP group as compared to Non-contact LP group (p=0.044). Conclusion Contact LP resulted in significant worsening of TBUT and increasing in OSDI sore. However, non-contact LP may not minimize the effect of laser on ocular surface of diabetic retinopathy patients. Appropriate care should be given to the ocular surface of diabetic retinopathy patients during LP procedure.